PENGARUH DISIPLIN BELAJAR TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN EKONOMI DI SMA SANTUN UNTAN - yarso, Meilany; Purwaningsih, Endang; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research was to find out how much influence the discipline of learning has toward student learning outcomes on economic subjects in  XI IIS 2 class at SMA Santun Untan. The method used in this research is descriptive percentage method with the form of research used is ex post-facto research. This research had all of the 29 students of XI IIS 2 class at SMA Santun Untan  as its population . In collecting the data, the researcher used indirect communication and documentary study technique. The tools of data collection used were questionnaire and docummentation. The technique of data analysis was descriptive and simple regression analysis. Based on the result from the t test that had been done,t value > t table (2,374>2,048) therefore, Ho was rejected and Ha was accepted which meant there was a significant positive effect between  the discipline of learning has toward student learning outcomes on economic subjects in  XI IIS 2 class at SMA Santun Untan . The results of the coefficient of determination (R2) amounted to 0.173 which meant the contribution of the effect between the discipline of learning  and student learning outcomes had 17,3%  meanwhile the rest was 82,7% which was affected by another factor that was not included in this research Keyword :Discipline of Learning, Student Learing Outcomes